Preparation, characterization and biological activities of egg white peptides-calcium chelate. (September 2021) - Huang, Wen; Lan, Yaqi; Liao, Wanwen; Lin, Li; Liu, Guo; Xu, Hanmei; Xue, Jianpeng; Guo, Baoyan; Cao, Yong; Miao, Jianyin
Abstract: The optimal conditions for preparation of egg white peptides-calcium chelate (EWPs-Ca) were determined by response surface methodology (RSM). Under the optimal condition (mass ratio of peptide: calcium of 4:1 at 53 °C and pH 8.2 for 30 min), the calcium content of EWPs-Ca was 44.1 mg/kg. The results of Ultraviolet–Visible absorption spectroscopy (UV) and Fourier transform infrared spectroscopy (FTIR) indicated that the carboxyl oxygen and amino nitrogen atoms of the egg white peptides (EWPs) may chelate with calcium during the chelation. Amino acid analysis suggested that glutamate, aspartic acid, cysteine, threonine, glycine and lysine played important roles during the chelation. The scanning electron microscopy showed that due to EWPs combined with calcium, the structure of EWPs-Ca became loose porous sponge. Moreover, the amount of transferred calcium of EWPs-Ca was 46.18 ± 2.12, 63.86 ± 0.36, 106.91 ± 0.44, 123.61 ± 1.59 μg/mL at 30, 60, 120, 180 min in Caco-2 cell monolayers, respectively. Compared with the blank control, the proliferation rate of Human fetal osteoblast (HFOB) cells reached the maximum value of 119.55 ± 1.36%, 110.20 ± 1.56% and 112.58 ± 1.62% at 24, 48 and 72 h, respectively and EWPs-Ca also improved the activity of alkaline phosphatase (ALP). Highlights: The optimal calcium chelation conditions of EWPs was obtained. Carboxyl oxygen and amino nitrogen of EWPs chelate with calcium during the chelation. EWPs-Ca could effectively enhance calcium transport in Caco-2 cell monolayers. EWPs-Ca had positive effect on HFOB cells.